Student Affairs's Voice, Visibility, and Relevance in Higher Education Administration. Issue 3 (3rd July 2019) - Ching, Doris; Agbayani, Amefil
Abstract: Many colleges and universities today are reorganizing student affairs operations in ways that eliminate or reassign many of their functions to other university departments. In some drastic cases, student affairs departments and senior leadership positions have been eliminated. On some campuses, the chief student affairs officer does not report directly to the chief executive officer and is not a cabinet member. The major reasons cited for these administrative actions include the following: to achieve greater integration of institutional services and programs; to reduce costs and/or redistribute funding to other institutional priorities; to reduce bureaucracy and layers of administration; and to make student services more streamlined and accessible to students. While these institutional actions may appear reasonable, they overlook the fundamental mission and role of student affairs in colleges and universities. Furthermore, they undermine the significant ways in which student affairs programs contribute to the educational success of students. Within these contexts, this article poses and addresses a necessary and timely question: When student affairs loses institutional visibility and its central role in the administrative structure, what essential elements of an institution's educational mission and priorities are lost?